"Chisel marks" on columnar joint face - Wojtal, Steven F. (Oberlin College Library, 1997)
An image of the side of a column from columnar joints. The surface is highly irregular, consisting of numerous curved and intersecting fracture surfaces. On many surfaces, clear plumose markings indicate the direction of fracture propagation, with some indicating right to left propagation (as the 4th and 5th fractures from the top right of the column) and others indicating left to right propagation (as second surface up from the flat rock in the foreground).